2004
DOI: 10.1111/j.1365-2958.2004.04050.x
|View full text |Cite
|
Sign up to set email alerts
|

Branching sites and morphological abnormalities behave as ectopic poles in shape‐defective Escherichia coli

Abstract: SummaryCertain mutants in Escherichia coli lacking multiple penicillin-binding proteins (PBPs) produce misshapen cells containing kinks, bends and branches. These deformed regions exhibit two structural characteristics of normal cell poles: the peptidoglycan is inert to dilution by new synthesis or turnover, and a similarly stable patch of outer membrane caps the sites. To test the premise that these aberrant sites represent biochemically functional but misplaced cell poles, we assessed the intracellular distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 42 publications
(71 reference statements)
4
56
0
Order By: Relevance
“…The shape abnormalities resulting from the overproduction of Mbl were associated with an altered helical pitch of the filaments, and Mbl was consistently clustered at the bases of bumps and bud-like morphologies but not at the tips of developed branches (12,13). For E. coli cells, it has been shown that PG (and outer membrane proteins) is stable at the poles and that the tips of branches behave as polar caps and are correlated with areas of inert PG (30,32,122). Thus, a strong correlation between the occurrence of cell wall active growth and Mbl clustering was suggested.…”
Section: Mreb-like Proteins and Cell Polaritymentioning
confidence: 90%
“…The shape abnormalities resulting from the overproduction of Mbl were associated with an altered helical pitch of the filaments, and Mbl was consistently clustered at the bases of bumps and bud-like morphologies but not at the tips of developed branches (12,13). For E. coli cells, it has been shown that PG (and outer membrane proteins) is stable at the poles and that the tips of branches behave as polar caps and are correlated with areas of inert PG (30,32,122). Thus, a strong correlation between the occurrence of cell wall active growth and Mbl clustering was suggested.…”
Section: Mreb-like Proteins and Cell Polaritymentioning
confidence: 90%
“…This polar peptidoglycan is "inert" in that it is neither degraded and recycled nor diluted by addition of new material (43,52,171). Interestingly, this same stability extends to proteins and lipopolysaccharides in the outer membranes of the poles of gram-negative bacteria (51,91,235) and to proteins on the surfaces of gram-positive organisms (239). These inhomogeneities among lipids, proteins, and peptidoglycan indicate that bacterial poles differ from the rest of the cell, which makes them prime candidates for hosting specialized functional elements.…”
Section: Sequestrationmentioning
confidence: 97%
“…Another indication linking FtsZ to cell shape determination was the observation that the formation of branches and abnormal cell shapes observed in mutants lacking LMW PBPs, notably PBP5 (42,134), was augmented when these mutants were studied in an ftsZ84(Ts) background (193). Mutant cells lacking PBP5 and another LMW PBP (the phenomenon was strictly PBP5 dependent) showed spiral morphology when FtsZ activity was blocked by overexpression of the FtsZ inhibitor SulA (193).…”
Section: A Reappraisal Of the Role Of The Tubulin Homologue Ftsz In Cmentioning
confidence: 99%